NEW NUTRIENT MEDIUM ON THE BASIS OF DRY FIBRIN HYDROLYSATE FOR V. CHOLERAE CULTIVATION - I. M. Zhulidov (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The data on exploration of biological properties of experimental solid and liquid media on the basis of dry enzymatic hydrolysate of fibrinobtained from production waste of anti-rabies immunoglobulin is presened here. The culture media engineered meets the requirements of normative documents and. is highly competitive with the test medium in their qualitative characteristics. Suggested media can be used for V. cholerae cultivation, including submerged cultivation, in production of cholera preventive and. diagnostic preparations.